Um olhar sociológico sobre a criança e o brincar: espaço e tempo de construção, reinvenção e aprendizagem - Estácio, Mércia Maria de Santi (2010)
This research I discuss the play, also talking with the other subjects that make up the universe in which the play is inserted, such as family, school and culture. The fundamental proposition of this dissertation assumes that the absence of play in children's lives affect their physical structure, psychological, biological, cultural, social, historical and theirs development. The initial questions were: What are the spacetimes reserved in the school for play? What is the importance of play in the development of children? Does the school recognize the importance of play in its social space? How the children perceive and use the spacetimes to play at school? Are there spacetimes at school to play? This is a theoretical and empirical research of exploratory study. The research‟s field was the Municipal School Professor Ulysses Góes, located in district of Nova Descoberta, in Natal, Rio Grande do Norte and, as research techniques, I used: participant observation, photography, structured interviews with students and questionnaires with teachers. The results indicate that for most of children, the school allows the play, few disagree with this preposition.Teachers recognize the importance of play in school, but for various reasons do not provide your practice. The dissertation points the possibility of new studies and developments for the theme.